127 Optimum Treatment for Sigmoid Volvulus Remains Elusive but Surgery May Provide Considerable Benefit: Results of a 5-Year Audit. (28th February 2022) - Issa, M.; Nair, D.; David, B.; Banks, J.; Lewis, E.; Monk, C.; Griffin, A.; Guy, R.
Abstract: Background: Sigmoid volvulus is a surgical emergency and patients are often elderly with significant comorbidities. Whilst endoscopic decompression is easy and effective in the short-term, recurrence and repeated admissions are common with surgery generally being reserved for non-resolution or complications. Consensus an optimum management is lacking. Method: A retrospective audit of all patients admitted with sigmoid volvulus to a DGH General Surgery service between 01/01/2015-20/10/2020 was undertaken. Patient demographics, comorbidities, clinical findings, investigations, and treatment were recorded. Results: Sixty-three patients were identified (median age 71.5 years; 58.7% male]. Some 50.8% had more than one previous presentation (range 1–6), 19% presented after 3 days of symptoms and 3.2% presented with perforation. Plain radiography and CT scanning was undertaken in 90.5% and 54%, respectively. Endoscopic detorsion was performed in 77.77% and repeated in the same admission for 33.3% of cases. Flatus tubes and rigid sigmoidoscopy was used in 47.6% with a 59.6% success rate. Seventeen patients (27%) underwent sigmoid resection, 14 having open surgery and 3 laparoscopic. Primary anastomosis was undertaken in 64.7% (11 patients), with only one anastomotic leak; the remaining 6 patients had a colostomy. The re-admission rate was 30.1% (19% non-operated patients, 11.1% operated patients). Conclusions: Most patients with sigmoid volvulus are managed non-operatively with endoscopic detorsion which may be associated with a considerable healthcare burden and high readmission rates. Selective resection can be associated with low morbidity and good outcomes. Clinicians could reasonably adopt a lower threshold for surgical intervention, particularly for recurrent volvulus.